Reflection of local cultural values behind loss accounting practices by ilabulo sellers - Mohamad Anwar Thalib (International Journal of Accounting and Management Information Systems, 2023)
Purpose: This study aims to reveal the non-material value behind the practice of loss accounting by ilabulo traders. Methodology/approach: This research uses the Islamic paradigm. The approach used is Islamic ethnomethodology. There are five data analysis stages: charity, knowledge, faith, revelation information, and courtesy. Results/findings: The study results show that traders avoid losses by distributing the leftover ilabulo to the local community for free. This accounting practice is conditional on the value of patience. In the Islamic culture of Gorontalo, the elders often internalize the value of patience through lumadu "mopo'o tanggalo duhelo" The meaning of this expression is the whole of patience. The implication of this research is to present the concept of loss accounting based on local wisdom values. Conclusion : This study concludes that ilabulo traders practice loss accounting based on the cultural and religious value of patience. By distributing unsold food to the community, traders embody local wisdom rooted in Islamic teachings and Gorontalo cultural expressions. This reveals that accounting practices at the grassroots level are not only economic but also deeply moral and communal. Limitations: The limitation of this research lies in the informants who have yet to provide information from the cultural experts. Contribution: The contribution of this research is that it can provide deeper insights into the local cultural values that influence the accounting practices of ilabulo traders. This can help us understand how culture plays a significant role in local-level accounting decision-making. Furthermore, the results of this research can be used to develop an accounting model that is more in line with the culture and local context of ilabulo traders. This can assist in designing more relevant and sustainable accounting practices.